2018 IFIP/IEEE International Conference on Very Large Scale Integration (VLSI-SoC) 2018
DOI: 10.1109/vlsi-soc.2018.8644846
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of test solutions for COTS-based systems in space applications

Abstract: One of the current trends in space electronics is towards considering the adoption of COTS components, mainly to widen the spectrum of available products. When substituting space-qualified components with COTS ones a major challenge lies in guaranteeing the same level of reliability. To achieve this goal, a mix of different solutions can be considered, including effective test techniques, able to guarantee a high level of permanent fault coverage while matching several constraints in terms of system accessibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…As a major result of this effort, it is now possible to compute the Fault Coverage achieved by a generic test step by considering a list of faults from which safe faults have been removed. For this purpose, we can use the Fault Coverage without Safe Faults (FC_safe) metric, as done already in [4], computed via the expression: FC_safe = #detected faults / (#faults -#safe faults) The proposed method for the identification of safe faults and for the calculation of the FC_safe is independent of the test method chosen to test the device. In our case study we chose to test the OR1200 CPU by resorting to a Self-Test Library (STL) based on the Software-Based Self-Test (SBST) paradigm.…”
Section: Safe Faults Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…As a major result of this effort, it is now possible to compute the Fault Coverage achieved by a generic test step by considering a list of faults from which safe faults have been removed. For this purpose, we can use the Fault Coverage without Safe Faults (FC_safe) metric, as done already in [4], computed via the expression: FC_safe = #detected faults / (#faults -#safe faults) The proposed method for the identification of safe faults and for the calculation of the FC_safe is independent of the test method chosen to test the device. In our case study we chose to test the OR1200 CPU by resorting to a Self-Test Library (STL) based on the Software-Based Self-Test (SBST) paradigm.…”
Section: Safe Faults Identificationmentioning
confidence: 99%
“…The set of Safe Faults for a given system includes the well-known Untestable Faults, that are usually caused by structural or sequential redundancy (which cannot be tested even by an exhaustive test) but it also contains faults that cannot produce any failure (and thus cannot be tested) due to the specific configuration of the system, which in some way limits the controllability and observability of each unit inside. It has been shown [4] that the percentage of Safe Faults may be significant (achieving 20% or 30% of the total number of faults in many cases), and it is thus crucial to be able to identify them. Similar figures have been obtained when analyzing the portion of a processor which is not used by a given application [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For those which are not detected we must rely on alternative analysis methods that can prove whether they could disturb safety-critical functionalities or not (Safe Faults). Previous works [4] showed that the number of Safe Faults can be significant in real applications. In complicated designs, manual analysis of fault effects is an arduous task that requires extensive knowledge of the design functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 5.15 and Figure 5.16 we compare test-programs generated using the proposed method with 274 T M Is against SBST programs P1 to P6 (details about these test programs can be found in [206,207]) in terms of stuck-at and transitionfault coverage. Test programs P1 to P6 have been generated manually, requiring several weeks of significant test-engineering effort.…”
Section: Evaluation Of Sbst Approachmentioning
confidence: 99%